Analisis Kejadian Katarak Pada Manusia Lanjut Usia Di RS Khusus Mata Masyarakat Provinsi Sumatera Selatan Tahun 2023 - Silfa Mardianita; Dianita Ekawati; Chairil Zaman (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
Cataracts are a loss of lens transparency resulting in a change in refractive properties and an increase in light scattering which causes blurred vision or blindness. The purpose of this study was to analyze the incidence of cataracts in elderly people at the Special Community Eye Hospital in South Sumatra Province in 2023. The design of this study was a quantitative cross-sectional approach. The population in this study were people who were treated at the Special Community Eye Hospital in South Sumatra Province, which consisted of 19,583 respondents. The sample in this study amounted to 100 respondents. How to take samples using purposive sampling. Data collection was carried out on 19-23 June 2023. Data collection using a questionnaire. Bivariate data analysis using the Chi-Square test. The results showed that there was a relationship between the incidence of diabetes mellitus (P Value 0.031), smoking habits (P Value 0.008), eye trauma (P Value 0.010), and a family history of cataracts (P Value 0.054), with the incidence of cataracts in elderly people at the Special Eye Hospital in South Sumatra Province in 2023. There was no work relationship (P Value 0.529), and gender (P Value 1.00) with the incidence of cataracts in the elderly at the Special Eye Hospital. Community of South Sumatra Province in 2023. It is hoped that health workers will provide counseling and education to the public about cataracts